Surface decoration of graphene with all-inorganic perovskite nanocrystals - Cottam, Nathan D. (2022)
Recent progress in the synthesis of high stability inorganic caesium lead halide perovskite nanocrystals (NCs) with unique optical and electronic properties has led to their increasing use in optoelectronic applications, such as broadband photodetectors. These NCs are of particular interest for the UV range as they have the potential to extend the wavelength range of photodetectors based on traditional materials. The physical properties of these nanostructures, such as the dynamics of charge carriers on different timescales and their effect on the optical recombination of carriers, are crucial for functional applications, but not yet fully understood.